Explaining Assessment Grades of First-Year Students in General Chemistry I at AUC: A Mixed-Methods Study - Soliman, Alaa (AUC Knowledge Fountain, 2026)
CHEM 1005 is the foundational chemistry course and a critical gateway for first-year AUC students seeking to join undergraduate programs at SSE. The course includes three milestone summative assessments: Exam 1, Exam 2, and the final exam. Students’ grades on these milestone assessments are critical to their academic careers, as they determine their major declaration decision. A decline of 5 points or more between Exams 1 and 2 poses substantial academic and personal challenges with serious consequences for students’ major declaration and academic trajectory. Although the Department of Chemistry at AUC has observed a consistent decline in some students’ Exam 2 grades over the past several academic years, it has neither investigated the reasons for this trend nor considered its implications for students’ academic careers at the university, highlighting a serious knowledge gap that urgently needs to be addressed to support this critical course. This mixed-methods study analyzed grade data from Fall 2021 through Spring 2025 (n=1600 students) and collected narratives from 16 former CHEM 1005 students who experienced a grade decline. This research found that a five-point decline in the average grades for Exams 1 and 2 persisted from Fall 2021 through Spring 2025.  Narratives from the 16 qualitative data participants indicate that students find Exam 2 content challenging, and some pedagogical elements were less effective for Exam 2. Moreover, around mid-semester, students face a heavier workload and competing courses, which shift energy and focus away from Exam 2 and lead many to experience negative emotions, including test anxiety, before and during the exam. The decline in Exam 2 grade affects the overall course grade. Sometimes, CHEM 1005’s grade harms the major declaration and academic trajectory, and sometimes not. This research contributes a more comprehensive definition of assessment in gateway courses that recognizes it as a complex institutional practice shaped by pedagogical design, student experiences, and high-stakes consequences, rather than merely a neutral measurement tool. The findings inform chemistry faculty at AUC to transform their pedagogy. Moreover, AUC needs to include “assessment literacy” in its FYE program and involve CSW to support first-year students during the stressful, high-stakes exam period by providing professional advice on time management and strategies for managing test anxiety, helping students focus on their studies and perform well on their exams.